2014
DOI: 10.1089/jir.2013.0088
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulatory Effects of Interferon-β in Suppression of Th17 cells

Abstract: To investigate the immunoregulatory effects of interferon (IFN)-β on CD4+ T cells, we examined the response of CD4+ T cells from IFN-β(+/+) and IFN-β(-/-) mice to CD3/CD28 activation and to differentiation to Th17 lineage, analyzing the expression of signaling effectors, cell surface receptors, production of IL-17, and gene expression profiles. We provide evidence of increased phosphorylation of the membrane proximal kinase associated with TCR activation, ZAP-70, in IFN-β(-/-) T cells compared with IFN-β(+/+) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 63 publications
1
15
1
Order By: Relevance
“…Th17 cell differentiation in humans is orchestrated by IL-1b and IL-23, which stimulate, and by IL-10 and IL-27, which inhibit the differentiation of this cell subset (Chen and O'Shea 2008;Volpe and others 2009;Segura and others 2013). Different reports have demonstrated that IFN-b can affect and inhibit at several levels the differentiation of Th17 cells both in the MS mouse model (Pennell and Fish 2014) and in MS patients. In particular, IFN-b therapy downregulated the expression of IL-1b and the p19 subunit of IL-23 in monocyte-derived DCs from MS-affected individuals and concomitantly induces the p28 subunit of IL-27 (Ramgolam and others 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Th17 cell differentiation in humans is orchestrated by IL-1b and IL-23, which stimulate, and by IL-10 and IL-27, which inhibit the differentiation of this cell subset (Chen and O'Shea 2008;Volpe and others 2009;Segura and others 2013). Different reports have demonstrated that IFN-b can affect and inhibit at several levels the differentiation of Th17 cells both in the MS mouse model (Pennell and Fish 2014) and in MS patients. In particular, IFN-b therapy downregulated the expression of IL-1b and the p19 subunit of IL-23 in monocyte-derived DCs from MS-affected individuals and concomitantly induces the p28 subunit of IL-27 (Ramgolam and others 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Female 2D2 mice, 6–12 weeks of age, were killed, their spleens were harvested and CD4 + T cells were positively selected using a CD4 + selection kit (Miltenyi Biotec) as described previously . The resulting CD4 + T cells were labelled with Cell Proliferation Dye 450 (eBioscience, San Diego, CA), at a concentration of 1 μ m , as per the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Mice that are IFN‐ β −/− have been used in EAE studies to validate the importance of IFN‐ β treatment in limiting the pathogenesis of the disease and in relapsing–remitting EAE, where there was evidence of increased frequency of relapses . We and others have shown regulatory roles for IFN‐ β in Th17 cell polarization . Treatment with IFN‐ β decreases IL‐17 gene and protein expression in proliferating murine CD4 + cells and prevents the elevation of IL‐17 mRNA in cells from the CNS draining LNs .…”
Section: Introductionmentioning
confidence: 99%
“…Regulation of CXCR4 surface expression may be part of the anti-viral activity of type I IFNs. Indeed, a downregulation of CXCR4-mRNA in human PBMC by in vitro exposure to IFN-a and IFN-g has been demonstrated [35], and mice deficient for IFN-b show increased CXCR4 expression on CD4 1 T cells [36]. Therefore, we asked whether altered CXCR4 surface expression could explain the inhibition of CXCL12-mediated T cell migration.…”
Section: Ifn-b1b Affects Cxcr4 Expression On T Cells In Msmentioning
confidence: 98%